2000
DOI: 10.1212/wnl.55.10.1450
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vagus nerve stimulation on respiration during sleep

Abstract: VNS is associated with adverse changes in respiration during sleep. In patients without preexisting OSA, this VNS effect is probably not clinically significant. In patients with preexisting OSA, VNS should be administered with care. Lowering VNS stimulus frequency or prolonging off-time may prevent exacerbation of OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
1
11

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(127 citation statements)
references
References 17 publications
4
111
1
11
Order By: Relevance
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In these studies, the number of patients included ranged from 1 to 60. Of these 15 articles, 4 involved only pediatric patients, 8,12,13,17 7 involved only adult patients, 4,5,10,11,[14][15][16] and 4 studies involved both adult and pediatric patients. 3,6,7,9 The patient ages ranged from 3 to70 years.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In these studies, the number of patients included ranged from 1 to 60. Of these 15 articles, 4 involved only pediatric patients, 8,12,13,17 7 involved only adult patients, 4,5,10,11,[14][15][16] and 4 studies involved both adult and pediatric patients. 3,6,7,9 The patient ages ranged from 3 to70 years.…”
Section: Methodsmentioning
confidence: 99%
“…18 A programming wand that communicates with the generator using radio frequency signals can be used to vary the output current, frequency, pulse width, and stimulation off and on time. 2 Additionally, a 50 gauss bar magnet provided by the manufacturer was reported in 8 studies [4][5][6][7]10,[14][15][16] and oxygen saturation was reported in 6. [4][5][6]10,15,16 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The common respiratory side effects of chronic vagal stimulation include dyspnea on exertion, altered breathing patterns (gasping), snoring during sleep, decreased airflow, and heightened respiratory effort during sleep. [40][41][42] In addition, one-third of patients with refractory epilepsy may have baseline obstructive sleep apnea (OSA). 43 A combination of respiratory side effects of chronic vagal nerve stimulation, residual anesthetic effects, and concomitant OSA may increase the risk of postoperative respiratory compromise.…”
Section: Magnetic Resonance Imaging Safetymentioning
confidence: 99%